Islamic Economic Market Mechanisms: From Prophetic Traditions to Classical Scholars’ Views and Their Role in Achieving SDGs (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This research explores the historical development and philosophical foundations of market mechanisms within Islamic economics by analyzing key ideas derived from the Prophet Muhammad’s practices and the intellectual contributions of prominent classical scholars such as Abu Yusuf, Al-Ghazali, Ibn Taymiyah, and Ibn Khaldun. By conducting a comprehensive literature review, the study traces how these early economic principles—rooted in ethical trade, social justice, fair pricing, and market regulation—have shaped the evolution of Islamic economic thought and how they remain relevant in addressing contemporary global challenges. The research underscores that many classical Islamic economic values—such as promoting equity, discouraging monopolies, ensuring transparency, and protecting the welfare of all market participants—align with several targets of the United Nations Sustainable Development Goals (SDGs), particularly those related to poverty reduction, responsible consumption, decent work, and reduced inequalities. The scholars examined in this study advocated for market interventions that upheld moral integrity, discouraged exploitation, and promoted the common good—principles that modern Islamic finance and economic policy continue to adopt. Furthermore, this study highlights that integrating these time-tested Islamic principles into modern economic frameworks can foster inclusive economic growth and more just resource distribution, both of which are crucial to sustainable development. The research affirms that Islamic economic thought, when contextualized within current global goals, offers a normative framework that balances material progress with moral accountability. Overall, this study argues that a renewed application of classical Islamic economic wisdom can offer practical and ethical solutions to modern financial and social challenges, and can significantly contribute to realizing the SDGs in both Muslim-majority and global contexts.